Characterisation and optical detection of puffy Satsuma mandarin. (May 2023) - Sun, Chanjun; Aernouts, Ben; Saeys, Wouter
Abstract : Puffiness is one of the dominant postharvest disorders in easy-peeling citrus cultivars. In this study, the structural changes between healthy and puffy Satsuma mandarin were investigated and the potential of using optical methods for disorder detection was explored. To gain more insight in this disorder, the external appearance and internal quality attributes were first compared between healthy and puffy Iwasaki Satsuma mandarins at three harvest times. Although no consistent differences were observed in the appearance of fruits, the soluble solids content and Brix minus acid values in puffy mandarin were found to be higher compared to the corresponding healthy fruit. The structural properties of the flavedo and albedo tissue layer in the peel were quantified from X-ray CT scans. Whilst no differences were observed in the size of the oil glands in the flavedo, the pore size in the albedo of puffy mandarin was found to be larger with later harvest. The bulk optical properties of the intact fruit were estimated from laser scatter images with a metamodel calibrated on optical phantoms. The reduced scattering coefficient ( μ s ' ) for the intact fruit was found to be lower in puffy mandarin relative to healthy fruit. The distinction between healthy and puffy mandarin based on μ s ' was further validated on Goku Wase Satsuma mandarin. The results obtained indicate that healthy and puffy mandarin can be separated well based on their μ s ' at all the selected wavelengths. This provides a basis for the non-destructive optical detection of puffing disorder at an early stage. Graphical abstract: Image 1 Highlights: External and internal attributes were compared between healthy and puffy mandarin. Thickness of both flavedo and albedo tissue layers was lower in puffy mandarin. Pore size in the albedo of puffy mandarin was larger at a later harvest time. The μ s ' of the intact fruit was lower in the puffy than the healthy mandarin.